DESENTRALISASI KEWENANGAN BIDANG PERTANAHAN BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2006 - Ilyas Ismail; Abdurrahman Abdurrahman; Muhammad Jafar; Azhari Azhari (Jurnal Media Hukum, 2010)
Law No. 11, 2006 concerning Aceh Government determines the existence of decentralization of authority in the land sector to the Aceh Government. However, in reality, the decentralization of authority could not be accomplished.  Therefore, this research aims at studying the authorities which have been decentralized and factors that led to the failure in implementing these authorities. The data were collected through literature research and field research. The literature research was conducted by reviewing the Law No. 11, 2006 and other statutory provisions as well as the views of relevant experts. Field research was conducted by interviewing officials of technical institutions and other relevant stakeholders. The results of the research show that the authorities in the land sector that are especially decentralized to the Government of Aceh through Law No. 11, 2006 are the autorithies to grand The Right to Cultivate and The Building Rights on Land. However, these rights have not been implemented due to the inavailability of more concrete rules and local officials whose fundamental duties and functions are specifically in the land sector.Key words: decentralization, authority, the land sector